Mainstreaming Sustainable Consumption of Seafood Through Enhanced Mandatory Food Labeling - Penca, Jerneja (Frontiers in Marine Science, 2020)
To contribute to the debate about sustainable seafood consumption this article considers the role of mandatory food labelling. The article first flags the rise of a policy paradigm of shared responsibility and policy imperatives at various levels calling for increased integration of the citizen/consumer into public regimes, including in fisheries governance. It then explores the options available to citizen/consumers to engage in the fisheries regime in different stages of the value chain and evaluates their readiness to respond to the expectations. Mandatory food labelling of seafood is introduced as an under-unexplored governance tool, alongside the key enabling technological and policy trends. While recognizing equity challenges and various supplementary actions needed to ensure an effective behavioural and attitudinal shift towards more engaged governance (education, enforcement, social setting), the article suggests to further explore mandatory labelling within the governance toolbox. It should be particularly relevant in the context of developed markets with global trade and political influence, and as means of fostering ocean literacy and transparent, participative and deliberative kind of governance.